Clerical Professionalisation and Catholic Enlightenment in the Polish-Lithuanian Commonwealth - Witecki, Stanisław (The journal of ecclesiastical history, 2025)
The article evaluates clerical professionalisation in the eighteenth-century Polish-Lithuanian Commonwealth by examining the division of labour within parishes. It argues that proponents of the Catholic Enlightenment endeavoured to achieve post-Tridentine reforms while also assigning to the clerical profession responsibilities for the material well-being of parishioners and service to the Commonwealth. It concludes that the process of clerical professionalisation remained incomplete. Firstly, approval for hiring assistant priests resulted in the delegation of many, if not all, ecclesiastical duties to them. Secondly, the improved professional education of priests occasionally led to unexpected withdrawal from pastoral duties seen as falling below their acquired competencies.